Rayleigh-wave group-velocity maps of Thailand, Myanmar and Malaysia derived from Ambient Noise Tomography with parameter testing - Saetang, Kasemsak; Srisawat, Wilaiwan (Bulletin of Geography. Physical Geography Series, 2025)
Ambient Noise Tomography (ANT) was employed using data from 52 seismic stations – 26 from the Thai Meteorological Network and 26 from surrounding networks, collected over a specific time frame. Dispersion curves were systematically stacked over three-month intervals to mitigate seasonal variations, accepting only those with SNR ≥ 2 and SD ≤ 0.1 km·s-¹. Rigorous parameter tests validated the methodology, which was found to be particularly appropriate for seismic investigations in the geologically complex regions of Thailand, the Malaysia Peninsula and the Thailand Peninsula, emphasising the Central Basin. The study generated detailed Rayleigh-wave group-velocity maps, revealing significant lateral variations in seismic velocities. High-velocity zones were predominantly associated with the Shan-Thai Terrane, whereas low-velocity areas were observed in Northern Thailand, the West-Burma Terrane and the Khorat Plateau. Comparative analysis with existing studies corroborates the validity of our methodology. The results provide a detailed characterisation of the seismic landscape, encompassing structures from the upper crust to deeper features such as the mid-crustal Conrad discontinuity. This study has wider implications for earthquake preparedness and resource exploration, while also acknowledging specific limitations associated with data constraints. Overall, this study affirms the effectiveness of ANT as an invaluable tool for seismic research in regions with intricate geological histories and active tectonic settings.